Change of direction deficit in national team Rugby Union players: Is There an influence of playing position? - Freitas, T. T.; Alcaraz, P. E.; Bishop, C.; Calleja-Gonzalez, J.; Arruda, A. F. S.; Guerriero, A.; Reis, V. P.; Pereira, L. A.; Loturco, I. (Sports, 2019)
The aim of this study was to investigate the change of direction (COD) ability and deficits of elite rugby union players, discriminating between position (backs and forwards), and between "faster and slower players", in multiple COD tasks. Twenty-four male rugby union players from the Brazilian senior National team completed the following assessments: Squat and countermovement jumps; drop jump; standing long jump, horizontal triple jumps; 40-m linear sprint; Pro-agility, L-Drill, and Zig-zag COD tests; and squat 1-repetition maximum. The differences between backs and forwards and between faster and slower performers were examined using magnitude-based inferences. Backs were faster (in both linear and COD speed tests) and jumped higher than forwards. Moreover, they generated an inferior sprint momentum. No differences were found in COD deficit between playing positions. However, when dividing the sample by median split, faster players outperformed their slower counterparts in all power-speed variables and presented higher COD deficits. These results suggest that separating rugby players by playing position might not discriminate players with different COD skills and that the median split analysis is more sensitive to identifying these differences. Furthermore, the present data indicate that faster rugby players are less efficient at changing direction and tolerating higher approach velocities in COD maneuvers.